Government Support and Social Media Impact on the Performance and Sustainability of F&B's MSME in Indonesia - Antesty, Sella; Susilawati, Made; Selan, Dwi Dersmi; Thalib, Najdah (IJBLE Scientific Publications Community Inc., 2023)
This study explores how government support and social media impact the performance and sustainability of small food and beverage businesses in Indonesia. The food and beverage (F&B) industry is vital for the country's economy, with MSMEs playing a key role. Despite challenges, the government is promoting Industry 4.0 to enhance the industry's competitiveness. MSMEs make a significant contribution to the F&B sector but face barriers like limited resources and the impact of events like the COVID-19 pandemic. This research looks at how government support and social media, when combined, influence these businesses. Using surveys and statistical analysis, the study finds a positive connection between government support and MSME sustainability and performance. Social media also shows a positive impact on sustainability and performance. The findings suggest the government should increase funding and support eco-friendly practices. MSMEs are encouraged to use social media for effective marketing, branding, and cost-saving, contributing to their overall success and sustainability. The study highlights opportunities for further research and a comprehensive evaluation of Indonesia's MSME ecosystem.